IMPLEMENTASI TEKNIK PARALLAX SCROLLING PADA ANIMASI 2D SEBAGAI MEDIA PEMASARAN SNACK BAROKAH: IMPLEMENTATION OF PARALLAX SCROLLING TECHNIQUE IN 2D ANIMATION AS A MARKETING MEDIUM FOR SNACK BAROKAH - Abdul Rohman; Yuli Purwati; M. Syaiful Amin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The increasing use of digital platforms is encouraging Micro, Small, and Medium Enterprises (MSMEs) to utilize more engaging promotional media to enhance the appeal of their products. However, many MSMEs still rely on conventional promotional methods that are visually unappealing and ineffective in reaching a wider audience. This study aims to implement parallax scrolling techniques in 2D animation as a promotional medium for the Snack Barokah MSME. This study employs the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collection, production, testing, and distribution. Data collection was conducted through interviews with the business owner as well as documentation regarding product information and promotional needs. The animation production process utilized Adobe Illustrator for creating visual assets and Adobe After Effects for assembling the animation by applying parallax scrolling techniques, thereby producing depth effects and dynamic visual movement. The research outcome is a 40-second promotional animation video with 1080p resolution, comprising seven main scenes showcasing product information and brand identity. The developed media was then tested using a questionnaire administered to 30 respondents representing the target audience. The evaluation results showed that the product recognition aspect received the highest average score of 4.76, indicating that the animated media effectively conveys product information. Overall, the developed animated media was assessed as having an attractive visual appearance and being effective as a promotional medium. Thus, the implementation of parallax scrolling techniques in 2D animation can be utilized as an effective digital promotional medium to increase product visibility and audience engagement for SMEs.